2019
DOI: 10.3892/etm.2019.7389
|View full text |Cite
|
Sign up to set email alerts
|

Immune regulation mechanism of vitamin�D level and IL‑17/IL‑17R pathway in Crohn's disease

Abstract: Immune regulation mechanism of vitamin D level and interleukin (IL)-17/IL-17 receptor (IL-17R) pathway in Crohn's disease was studied. Of 40 clean mature healthy rats, 10 rats were used as control group based on random number table, the remaining 30 rats to establish Crohn's disease rat models. After successful modeling, 30 rats were divided into model group, low-dose group and high-dose group with random number table. On the 1st day after modeling, rats in low-dose group were given a single dose of 1,750 IU o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
(30 reference statements)
0
7
0
Order By: Relevance
“…This was accompanied by lower levels of IL-17, IL17R, and Th17 cells in the colonic mucosa, suggesting that vitamin D may alleviate CD-induced inflammation by inhibiting the IL-17/IL-17R pathway, thus improving immune function and reducing disease severity. 87 Interestingly, a randomized controlled trial (RCT) showed that treating pregnant women with 2000 IU vitamin D daily can increase regulatory T cell immunity by enhancing the percentage of Treg and IL-10 + CD4 T cells in the peripheral blood. 88 In addition, vitamin D can enhance Treg function by increasing IL-10, TGF-β, FoxP3, and CTLA4 production thereby suppressing inflammation.…”
Section: Vitamin D and Ibd Pathogenesismentioning
confidence: 99%
“…This was accompanied by lower levels of IL-17, IL17R, and Th17 cells in the colonic mucosa, suggesting that vitamin D may alleviate CD-induced inflammation by inhibiting the IL-17/IL-17R pathway, thus improving immune function and reducing disease severity. 87 Interestingly, a randomized controlled trial (RCT) showed that treating pregnant women with 2000 IU vitamin D daily can increase regulatory T cell immunity by enhancing the percentage of Treg and IL-10 + CD4 T cells in the peripheral blood. 88 In addition, vitamin D can enhance Treg function by increasing IL-10, TGF-β, FoxP3, and CTLA4 production thereby suppressing inflammation.…”
Section: Vitamin D and Ibd Pathogenesismentioning
confidence: 99%
“…Statistical analysis revealed a significant difference in IL-17 expression between the endometriosis mice model given vitamin D at a dose of 24 IU and mice not given treatment. At serum vitamin D levels greater than 20 ng/ml, vitamin D supplementation is known to regulate IL-17 and improve the profile of various autoimmune diseases ( Bruce et al, 2011 ; Joshi et al, 2011 ; Bhargava et al, 2015 ; Aly et al, 2017 ; Xia et al, 2019 ; Ghorbani et al, 2021 ; Mahmoud et al, 2021 ). Roffe-Vazquez et al (2019) discovered a negative relationship between serum vitamin D levels and IL-17A.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D immunomodulation of IL-17 can occur through a decrease in the number of IL-17-producing cells, inhibition of CD4+ T cell differentiation into Th17 cells, and a repressive effect on IL-17 expression ( Bruce et al, 2011 ; Joshi et al, 2011 ). The repressive effect is caused by the vitamin D receptor’s transcription suppression mechanism, which inhibits the Il-17/Il-17R pathway ( Joshi et al, 2011 ; Xia et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An inverse relationship between Vit. D and IL-17 levels in other autoimmune diseases have also been reported [40,41], But so far, the exact mechanism of the relationship between the decrease in Vit. D levels and the increase in IL-17 levels in autoimmune diseases, especially rheumatoid arthritis, have not been determined.…”
Section: Discussionmentioning
confidence: 99%